Aortic stenosis in patients with kidney failure: Is there an advantage for a PD-first policy?. Issue 2 (March 2021) - Candellier, Alexandre; Hénaut, Lucie; Morelle, Johann; Choukroun, Gabriel; Jadoul, Michel; Brazier, Michel; Goffin, Éric
Aortic stenosis (AS) is the most common valvular disease. It is twice as prevalent in patients with kidney failure as compared to the general population. In addition, AS progresses at a faster rate and is associated with a higher risk of death and poorer quality of life in patients on dialysis. Chronic kidney disease–mineral and bone disorder (CKD-MBD), inflammation, and hemodynamic disturbances contribute to the pathophysiology and progression of AS. Whether the type of dialysis modality, that is, hemodialysis (HD) versus peritoneal dialysis (PD), has a differential impact on the development and progression of AS in patients with kidney failure remains debated. Recent data indicate that the prevalence of valvular calcifications might be lower and the development of AS delayed in PD patients, as compared to those treated with HD. This could be accounted for by several mechanisms including reduced valvular shear stress, better preservation of residual kidney function (with better removal of protein-bound uremic toxins and CKD-MBD profile), and lower levels of systemic inflammation. Given the high morbidity and mortality rates related to interventional procedures in the population with kidney failure, surgical and transcatheter aortic valve replacement should be considered in selected patients with severe AS. Strategies slowing down the progression of aortic valve remodeling should remain the cornerstone in the management of individuals with kidney failure and mild to moderate AS. This review explores the potential benefits of PD in patients with kidney failure and AS and provides some clues to help clinicians in the decision-making process when options for kidney replacement therapy are considered in patients with AS.